Pengaruh independensi, obyektifitas,Kompetensi, dan etika terhadap kualitas audit( Studi Empiris pada Inspektorat Eks Karesidenan Pati) - Prayoga, Bahtiar Fahmy; , Drs. Wahyono, Ak, M.A, CA (2016)
The audit quality is the auditor's work in examining the financial statements properly and adhere to established standards. Audit quality is determined by two things: independence and competence. The purpose of this study is to test the influence of the independence, objectivity, competence and ethics on audit quality. The population in this study are civil servants Inspectorate Ex Pati residency. The method to collected samples by using purposive sampling. The sample used in this study were 45 respondents. Data analysis is using multiple linear regression analysis. Results showed that R2 values obtained 0,729 which means 72.9% of audit quality is affected by the independence, objectivity, competence and ethics. The remaining 27.1% influenced by variables outside the model. T test results showed that the objectivity, competence and ethical effect on audit quality. While independence has no effect on audit quality.